Virulence of the Entomopathogenic Fungi Metarhizium spp. From Various Rhizosphere Against Pest Walang Sangit (Leptocorisa acuta thunb.) - Effi Yudiawati (Baselang, 2021)
Virulence of the Entomopathogenic Fungi Metarhizium spp. from Various Rhizospheres Against the Pest Walang Sangit (Leptocorisa acuta Thunb.). Metarhizium spp. is a type of entomopathogenic fungus that can be used to control Leptocorisa acuta. The purpose of this study was to obtain isolates of the fungus Metahrizium spp. which is virulent from various rhizospheres against L. acuta. The results of this study are expected to produce bioinsecticides with active ingredients from the entomopathogenic fungus Metahrizium spp. which are effective for controlling L. acuta pests in rice plants. Entomopathogenic fungal isolates Metarhizium spp. The samples used came from various plant rhizospheres in different regions, namely Met1a (Metarhizium spp. from the leek rhizosphere, Tanah Datar area), Met3b (Metarhizium spp. from the leek rhizosphere, Pua Agam River area), MetcTd (Metarhizium spp. from red chili rhizosphere, Tanah Datar area), Met2d (Metarhizium spp. from leek rhizosphere, Padang Lua Agam area), and MetKtBs (Metarhizium spp. from peanut rhizosphere, Batusangkar area). The results showed that some isolates of the entomopathogenic fungus Metarhizium spp. had a very significant effect on the mortality of L. acuta nymphs, L. acuta imago formed and duration of death of L. acuta. Treatment C (Met3b: Metarhizium spp. from leek rhizosphere, Pua Agam River area) was the best treatment among other treatments, with the mortality of 3 instar L. acuta nymphs of 100%, the number of imago formed 0% and the duration of death of 3 instar L. acuta nymphs with an average time of 4.50 days.